2014
DOI: 10.1016/j.clim.2014.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Cadherin-11 mRNA transcripts are frequently found in rheumatoid arthritis peripheral blood and correlate with established polyarthritis

Abstract: Rheumatoid arthritis (RA) synovial fibroblasts hyperexpress the mesenchymal cadherin-11, which is involved also in tumor invasion/metastasis, whereas anti-cadherin-11 therapeutics prevent and reduce experimental arthritis. To test the hypothesis that cadherin-11 is aberrantly expressed in RA peripheral blood, 100 patients (15 studied serially) and 70 healthy controls were analyzed by real-time reverse transcription-PCR. Cadherin-11 mRNA transcripts were detected in 69.2% of moderately/severely active RA, versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 25 publications
1
11
0
Order By: Relevance
“…Cdh11 ‐deficient mice have hypoplastic synovia and show reduced inflammation and cartilage erosion when challenged in an inflammatory arthritis model. Cadherin 11 is minimally expressed in immune cells , and anti–cadherin 11 antibody reduces arthritis severity in mice . A humanized monoclonal antibody targeting cadherin 11 has been evaluated in a phase I tolerability study (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…Cdh11 ‐deficient mice have hypoplastic synovia and show reduced inflammation and cartilage erosion when challenged in an inflammatory arthritis model. Cadherin 11 is minimally expressed in immune cells , and anti–cadherin 11 antibody reduces arthritis severity in mice . A humanized monoclonal antibody targeting cadherin 11 has been evaluated in a phase I tolerability study (Table ).…”
Section: Introductionmentioning
confidence: 99%
“…As suggested recently, mesenchymal CDH11 may drive migration of solid tumours to the bone and trigger osteoclastogenesis via homophylic interactions of cancer cells with osteoblasts and other bone marrow (BM) stromal cells (Shiirevnyamba et al , ). More recently, we reported that CDH11 might be expressed on rare circulating cells of haematopoietic origin in the peripheral blood (Sfikakis et al , ).…”
mentioning
confidence: 99%
“…CDH11 mRNA expression was determined in myeloma cell lines (L363, JJ‐N3, MR20 and H92), as well as in samples from MM patients’ blood (3 ml), as previously described (Sfikakis et al , ). Forty‐two patients with symptomatic MM, of whom 10 were examined serially, were studied.…”
mentioning
confidence: 99%
“…Proinflammatory cytokines upregulate CDH11, and then promote FLS homophilic interaction mediated by CDH11, leading to inflammation aggravation and diffusion [22]. CDH11 is a potential therapeutic target for RA [28]. However, another study showed that CDH11 targeting regimen was not suitable for RA treatment [29].…”
Section: Rheumatoid Arthritis (Ra) and Cdh11mentioning
confidence: 99%